Sistem Monitoring Jaringan Load balancing Dengan Metode Equal Cost Multipath (ECMP) Menggunakan Media Telegram - Mochammad Irfan Oktavianto; Yanuar Risah Prayogi (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
This riset discusses the Equal Cost Multi Path (ECMP) monitoring system that balances network loads using telegram bots, load balancing on networks is a technique of combining more than 1 server to share the load evenly. The use of telegram bot as a monitoring system, makes it easier to find out in real time when the server has a problem. By testing QOS (Quality of Service) on ECMP load balancing using 5 clients with 3 servers, when one server goes down the router will access the bot using the active server and send messages to the recipient of the message from the bot. From this research, it is known that 75% the monitoring system can run on ECMP load balancing. Keywords— Network, Load balancing ECMP, Monitoring System, Telegram Bot